Developing a procurement support tool for a laundry soap bar manufacturing facility in Venezuela - Marcano Diaz, Miguel Angel (Kansas State University, 2008)
Laundry bar soap has been produced commercially in Venezuela for over a century and is one of the most important products for beauty and personal care throughout the Venezuela. More than 10 Venezuelan companies produce and sell it, but two companies hold almost 85 percent of the market share, with the Las Llaves brand, alone, holding nearly 70 percent. Management for Las Llaves is concerned about how to remain competitive not only with quality and acceptance of its product (effectiveness) but also with how to produce the soap efficiently (at the lowest possible cost) to remain competitive in today's global economic environment. The objective of this thesis is to identify and analyze the sourcing costs of three raw ingredients used to produce laundry bar soap in the Las Llaves facility and to provide a model scenario to support the decision making analysis within the purchasing department.
Keywords: Economic Procurement Modeling; Commodity Procurement; Venezuelan Business Environment; Risk Management; Business Administration, General (0310); Business Administration, Management (0454); Economics, Agricultural (0503)